Social Skills Development in Bilingual Preschoolers : A Case Study - Tayebeh Sohrabi; Kimberly Maich (Canadian Society for Studies in Education, 2021)
This study presents a case study of bilingual preschoolers' social skills development in dimensions of communication, cooperation, emotional management, and problematic behaviours. This study utilized non-participation observation and semi-structured interviews for collecting data. Five bilingual preschoolers and two early childhood educators participated in this study. The results indicate that the main reason for bilingual children's exclusion is their language limitations rather than their appearance or other factors that would contribute to them being considered an outsider. The main barrier in the social skills development of bilingual children seems to be negative feelings such as frustration and hesitation that this group of children experience in relationships with others and inhibit them from interacting with others. The role of early childhood educators, peers, and parents in this group of children's social skills development is important.